AC Conductivity and Dielectric Relaxation Behavior Studies of 2-Acrylamido 2-Methyl Propane Sulphonic Acid (AMPS) with Amide Copolymers: Composition Dependence (International Journal of Innovative Research in Engineering & Management, 2022)
A systematic measurement of dielectric  constant (ε) and loss (tanδ) on powder pressed pellets of MAA with AMPS copolymers in composition10/90,20/80  and 50/50 have been carried out in the frequency range 200Hz – 100 kHz and in the temperature range from room temperature to180oC covering through the glass  transition temperature (Tg). Relaxation peaks were  observed (above Tg )from tanδ versus temperature curves.  The peaks are attributed to α – relaxations. Further the  peaks shift towards higher temperatures for higher  frequencies. The AC conductivity has also been evaluated  from the data. The results are discussed in the light of substituent effect in the copolymer.
Keywords: Dielectric constant (ε); Dielectric loss (tanδ); AC conductivity; Relaxation; segmental motion